Radioimmunoimaging and targeting treatment in an immunocompetent murine model of triple‐negative breast cancer using radiolabeled anti–programmed death‐ligand 1 monoclonal antibody. (4th July 2018) - Pang, Xiaoxi; Liu, Meng; Wang, Rongfu; Liao, Xuhe; Yan, Ping; Zhang, Chunli
Abstract : The overall aim of this study was to evaluate whether iodine‐131 radiolabeled monoclonal antibody (mAb) targeting programmed death‐ligand 1 (PD‐L1) can be used for imaging of PD‐L1 expression noninvasively in vivo and playing synergistic effect combined with immunotherapy. Anti‐PD‐L1 mAb was radiolabeled with iodine‐131 ( 131 I‐PD‐L1 mAb) and was characterized in vitro. Biodistribution and imaging in vivo were performed periodically. Therapy study was conducted in triple‐negative breast cancer–bearing BALB/c mice. As results, the labeling efficiencies of 131 I‐PD‐L1 mAb reached 80% ± 3%, with radiochemical purity of 97% ± 1%. 131 I‐PD‐L1 mAb preserved the capacity to bind living PD‐L1‐expressing cells specifically in vitro. Tumor radioactivity uptake of 131 I‐PD‐L1 mAb was significantly higher than that of control groups. The xenografts were clearly imaged from 48 to 72 hours noninvasively after injection of 131 I‐PD‐L1 mAb, while the xenografts were not imaged in control groups. Tumor growth was significantly inhibited, and median survival time was remarkably prolonged in combination therapy group compared with control groups. It was concluded that 131 I‐PD‐L1 mAb can be a potential theranostic candidate for visualizing of PD‐L1 expression noninvasively and performing synergistic therapy in carcinomas. Abstract : Although blockade the PD‐1/PD‐L1 checkpoint pathway is a promising cancer treatment, a significant number of patients do not respond to this therapy. It is critical to develop a theranostic probe to accurately assess dynamic immune checkpoint expression noninvasively and to potentially conduct synergistic therapy. In this study, we establish that 131 I‐PD‐L1 mAb can be used for detecting PD‐L1 expression in malignant tumors or metastasis lesions in vivo and showing encouraging therapy effects when combining with immunotherapy.